2023
DOI: 10.3390/ijms24032136
|View full text |Cite
|
Sign up to set email alerts
|

Immunopharmacological Activities of Luteolin in Chronic Diseases

Abstract: Flavonoids have been shown to have anti-oxidative effects, as well as other health benefits (e.g., anti-inflammatory and anti-tumor functions). Luteolin (3′, 4′, 5,7-tetrahydroxyflavone) is a flavonoid found in vegetables, fruits, flowers, and herbs, including celery, broccoli, green pepper, navel oranges, dandelion, peppermint, and rosemary. Luteolin has multiple useful effects, especially in regulating inflammation-related symptoms and diseases. In this paper, we summarize the studies about the immunopharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 145 publications
0
13
0
Order By: Relevance
“…[34] More and more studies have shown that luteolin can be used to treat gouty arthritis, diabetes, tumors, and cardiovascular and cerebrovascular diseases. [35][36][37][38][39] Researchers found that luteolin can reduce joint synovial hyperplasia, cartilage, and bone erosion in GA rats. [40] Luteolin reduces the expression of MyD88 by regulating TLR4 receptors, thereby inhibiting the expression of NF-κB-related proteins, reducing the release of related inflammatory factors, and alleviating the inflammatory cascade, thereby protecting joints.…”
Section: Luteolinmentioning
confidence: 99%
“…[34] More and more studies have shown that luteolin can be used to treat gouty arthritis, diabetes, tumors, and cardiovascular and cerebrovascular diseases. [35][36][37][38][39] Researchers found that luteolin can reduce joint synovial hyperplasia, cartilage, and bone erosion in GA rats. [40] Luteolin reduces the expression of MyD88 by regulating TLR4 receptors, thereby inhibiting the expression of NF-κB-related proteins, reducing the release of related inflammatory factors, and alleviating the inflammatory cascade, thereby protecting joints.…”
Section: Luteolinmentioning
confidence: 99%
“…Luteolin targets human telomerase reverse transcriptase, which can stop BC cell growth and the development of tamoxifen resistance in BC. Therefore, it can be a potential natural medication to prevent BC invasion and metastasis [ 26 ].…”
Section: Anticancer Properties Of Luteolin and Its Mechanism Of Actionmentioning
confidence: 99%
“…The anti-inflammatory activity of LUT is achieved at micromolar concentrations by inhibiting the expression of COX-2 and the production of several pro-inflammatory mediators such as TNF-α and IL-6, hindering macrophage activation and release of excessive amounts of PGs [ 101 , 105 ]. Moreover, LUT can also regulate several signal transduction pathways, including NF-κB, AP1 and JAK–STAT [ 106 ], and it can inhibit macrophage recruitment to the endometriotic lesions by suppressing the secretion of CCL2 and CCL5 by endometriosis cells [ 101 ]. In a recent molecular docking study, it has been shown that LUT inhibits inflammation in EMS acting on signal transducer and activator of transcription 3 (STAT3), phosphoinositide-3-kinase regulatory subunit 1(PIK3R1), and mitogen-activated protein kinase 1 (MAPK1), also regulating MAPK, PI3K, TNF, and NF-κB signal transduction [ 107 ].…”
Section: Natural Substance Anti-inflammatory Propertiesmentioning
confidence: 99%